Enxergar a dança, descortinar o corpo: caminhos para a prática da dança com o corpo (d)eficiente visual - FEIO, Thalita Aires dos Santos (2018)
Instigated the search for understanding of blind people in dance education, I propose as a general objective of this research to investigate possible ways to start the practice of dance education for students with visual impairment. The research methodology is based on the phenomenology related to the study of perception and reasoning in Maurice Merleau-Ponty’s studies (2006).The documentary research is qualitative, because I realized bibliographic studies on educational activities of authors who have worked with the research of dance and blind people with other disabilities: Fatima Daltro (2005), Saulo Silveira (2009), Marina Mota (2013), Clotildes Cazé and Adriana Oliveira (2008), Jennifer Nascimento (2013), among others. These theorists wants to understand through research how is the integration of people with disabilities in dance and the possibilities for learning and creation. To study the body through teaching methodologies with holistic character, I used theoretical as: Moshe Feldenkrais (1997), Dianne Woodruff (1999), Enamar Ramos (2007), Klauss Vianna (2005), Jussara Miller (2012). On the understanding of visual impairment, I used the writings of: John Ganzarolli Vicente de Oliveira (2002), José Veiga Espinola (1983), Ruth Tolocka, Rozangela Verlengia and colabs (2006). Theoretical methodology’s research are: Antonio Carlos Gil (1989), Eva Lakatos and Marina Marconi (2005). Another mechanism of data collection for this study was an open structured interview conducted with the teacher / director Marina Alves Mota and one of her dancers of Passos Para Luz’s dance group from Belém do Pará. Seeking researching the influences exerted by the dance about ballerina’s perception of itself, the environment and other bodies, and how this influence reverberates in building the autonomy of the person who does not see, but sees through other lenses. These results are surprising about the possibilities of learning visually impaired person in the dance and how it can exert significant changes in the lives of these individuals.